(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the problem of the key tasks of ensuring the implementation of the rights of citizens in the field of business activity. In general, the tasks of ensuring the realization of citizens’ rights in the field of entrepreneurial activity are derived from the tasks of the economic policy of the state in the field of economic activity. This is due to the fact that entrepreneurial activity is a type of economic activity. At the same time, the task of ensuring the rights of citizens in the field of entrepreneurship is specific due to the nature of this activity (in particular: systematicity, independence, riskiness, etc.), as well as its importance for the socio-economic stability of the state. It is substantiated that the task of ensuring the realization of the rights of citizens in the field of entrepreneurial activity should be characterized as the legally defined results of the activities of the entities authorized to do so, the achievement of which should lead to the unimpeded development of entrepreneurship as the basis of the economic well-being of the country. Among such tasks, several levels can be distinguished: firstly, general legal tasks: 1) recognition and promotion of the realization of rights, primarily through the implementation by state authorities, local self-government bodies, and their officials of the powers provided for by law; 2) unobstructed realization based on non-interference in the process of realization of these rights without grounds established by law; 3) protection of rights from illegal encroachments by other holders of such rights (in particular, restriction of monopoly, creation of conditions for fair competition), and by other persons; secondly, economic and economic, which flow from the main directions of the economic policy of the state in the sphere of economic activity. thirdly, special - determined by the specifics of specific law in the field of entrepreneurial activity.